Digestibility of swine liver and meat protein hydrolysates by Nile tilapia - dos Santos Cardoso, Matheus [UNESP]; Nettson, Luciana Valéria; de Freitas, Jaqueline Marcela Azambuja; Lewandowski, Vanessa; Signor, Altevir; Boscolo, Wilson Rogério; Bittencourt, Fábio (FapUNIFESP (SciELO), 2022)
The objective of this work was to evaluate the digestibility of the protein, amino acids, and gross energy of swine liver and meat hydrolysates by Nile tilapia (Oreochromis niloticus). The fish were distributed into 12 tanks with conical bottoms, in a completely randomized design, and fed with the three following diets, with four replicates each: a reference diet with soybean and fish meal; and two test diets, one with swine liver hydrolysate and the other with swine meat hydrolysate. The coefficients of apparent digestibility were high for both hydrolysates, being above 83% for dry matter, 95% for crude protein, and 92% for gross energy. Regarding amino acids, the coefficients remained at 98–100% for the two hydrolysates. The digestibility percentages of the hydrolysates were higher than those of the protein ingredients, both of plant and animal origin, commonly used in the formulation of diets for this fish species. The tested hydrolysates have potential to be used in the formulation of diets for Nile tilapia.
Digestibilidade de hidrolisado proteico de fígado e carne suínos pela tilápia-do-nilo
Keywords: animal by-products; aquaculture; digestible nutrients; Oreochromis niloticus; protein hydrolysate